DESCRIPTIVE ANALYSIS OF THEORY AND IMPLEMENTATION OF MARKETING PLAN: PERSONAL SELLING PROGRAM (CASE STUDY AT SUBANG HOSPITAL) - Gugyh Susandy; Aulia Putri Faujiah; Hanifah Zahra Ramdhani; Rini Nuraeni (STIESA-PRESS, 2023)
Subang Regional Hospital is a hospital located in Subang, West Java, Indonesia. This case study was conducted to describe the situation and operational conditions of the hospital in terms of health services, infrastructure and general performance. First of all, it is important to understand the context of the Subang District Hospital in facing the challenges of health services in its region. Subang is an area that has a population of around 278?696.2 thousand people from the Central Statistics Agency and often experiences a surge in the need for health services. Therefore, Subang Regional Hospital is an important institution that is responsible for providing quality health services for the local community. This research method uses a descriptive qualitative approach to literature study, the data that has been collected will be analyzed more deeply in a qualitative descriptive manner.